Trends in research related to ophthalmic microperimetry from 1992 to 2022: A bibliometric analysis and knowledge graph study - Ming, Jing; Qin, Rui (Frontiers in Medicine, 2023)
Background: Microperimetry is a novel technology to assess the macular function. The aim of the study was to explore global research status and trends on microperimetry. Methods: Documents related to microperimetry in ophthalmology between 1992 to 2022 were extracted from the Science Citation Index Expanded (SCI-E) database of the Web of Science Core Collection (WOSCC). Raw data were analyzed using the VOSviewer and CiteSpace software. Bibliometric parameters included annual publication quantity, countries, authors, journals, international cooperation and keywords. Results: A total of 1217 peer-reviewed documents were retrieved. Annual research output has increased significantly since 2005, especially from 2013. Holz F, Rubin G and Guymer R contributed most to the number of articles published about microperimetry. Respectively, Rubin G, Fitzke F and Holz F received the most citations for their work. Countries publishing most were the USA, Italy and the UK, while the USA, the UK and Germany received the most citations frequency. Univ Bonn, UCL and Moorfields Eye Hosp were the top 3 productive institutions for microperimetry research in the world. The top 3 journals that publish articles about microperimetry were Retina-The Journal of Retinal and Vitreous Diseases, Investigative Ophthalmology & Visual Science and American Journal of Ophthalmology. The top 10 common keywords included microperimetry, optical coherence tomography, eye, retinal sensitivity, macular degeneration, fundus autofluorescence, scanning laser ophthalmoscope, visual-acuity, sensitivity and degeneration. Keywords “optical coherence tomography angiography”, “retinitis pigmentosa” and “internal limiting membrane” bursted in recent 3 years. Conclusions: The bibliometric and knowledge graph analysis of research status and trends in microperimetry provided global researchers with valuable information to propose future cooperation and track cutting-edge progress.